وقف النخيل في عمان: دراسة فقهية في الاهتمام والأغراض والتحديات والحلول من خلال الاستفتاءات والوصايا في كتب الفقه والفتوى (القرن ١٢ه-١٥ه/ ١٨م-٢١م) - البطاشي, هلال بن خلفان (مجلة كلية الدراسات الإسلامية والعربية للبنات بالزقازيق, 2025)
Keywords: Agriculture – Oman; Waqf (fondations) – Oman

الأرض والزراعة في عُمان من خلال كتاب المصنف للشيخ أحمد بن عبد الله الكندي النزوي (ت: 557ه/1162م) - القدحات, محمد بن عبد الله (‏ملامح من تاريخ وحضارة مدينة نزوى: ‏البحوث المقدمة في بدوة نزوى تاريخ وحضارة (2-4 ‏نوفمبر 2015), 2021)
Don (Mascate, novembre 2022)
Keywords: Agriculture – Oman

Hydraulic of sustainable groundwater resources, aflaj in Oman, using meshless numerical method - Mohtashami, Ali; Ghafri, Abdullah Saif Al- (Acta Geophysica, 2024)
Aflaj refers to a traditional irrigation system found in Oman, which has been used for centuries to sustainably manage groundwater resources. These resources play a vital role in meeting various consumption needs, including agriculture, domestic, and industrial. The article, for the first time, introduces the concept of “hydraulics of aflaj”, emphasizing the importance of accurate information about interaction of falaj and aquifer and also flow within their tunnels. The study utilizes the mechanisms of horizontal wells to simulate the interaction between the aquifer and the falaj tunnel, employing the meshless local Petrov–Galerkin numerical model to compute groundwater head of aquifer. The model is applied to a real test case in the Loba aquifer of Malaysia, demonstrating improved accuracy compared to previous models based on evaluation indices such as MAE, RMSE, MAPE, NSE and p-bias. The findings of the proposed model show good agreement.
Keywords: Agriculture – Oman

Hydro-tribalism: water and intra/inter group cohesion in the rural regions of Oman - Khaneiki, Majid Labbaf; Ghafri, Abdullah Saif al-; Saadi, Nasser al-; Abri, Zahra Saif al- (GeoJournal, 2024)
This article examines falaj system in relation to the tribal fabric of its beneficiary community. Falaj is a gently sloping underground tunnel or open channel that transfers groundwater or seasonal runoffs to the cultivated lands. Falaj acts as a core around which six socio-economic spheres form in a certain spatial order: shari’a public space, residential area, orchards, farmlands, pastures, and eventually falaj socio-economic hinterland. These spheres are the products of a systematic interaction between falaj, tribal communities and their economy. This article looks into the role of water in social cohesion within local communities and cooperation between tribal territories, which is conducive to the Omani variation of tribalism based on blood, soil and water. This type of tribalism is called hydro-tribalism whose socio-economic integrity is systematically contingent on accepting others in the group and cooperating with other groups. Some scholars mistakenly use the metaphor of “salad fabric” to describe Oman’s tribal composition, where different tribes live in harmony within the same territory but never melt into a homogeneous unity. However, this article likens hydro-tribalism to “solar system” where different groups remain in the orbits of their own tribal identities around a central falaj system, in the form of a complex socio-economic organization. This article concludes that falaj system is crucial in Oman’s sustainable development not only for the water that it can still supply to the country’s oases, but also for its social function that has always served to cement an organic relationship between different pieces of Oman’s social mosaic.
Keywords: Agriculture – Oman